Didactic Features of Improving Pedagogical Skills of Preschoolers Based on an Integrative Approach (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The introduction of innovations into the education system, the effective use of modern pedagogical technologies are important tasks of modern education. This article discusses the methods of developing students' pedagogical skills based on an integrative approach.